THE ANALYSIS OF STUDENTSâ€™ CRITICAL THINKING IN JUNIOR HIGH SCHOOL MEASURED BY SCIENCE VIRTUAL TEST (SVT) - Rusyati, Lilit (Jurnal Pengajaran MIPA, 2018)
This descriptive research described a profile of studentsâ€™ critical thinking that measured by Science Virtual Test (SVT). The participants who involved in this study are 563 students on Junior High School (JHS). Their distibution are 188 students in 7th grade (13 years old), 265 students in 8th grade (14 years old), and 110 students in 9th grade (15 years old). They comes from Bandung city, Bandung district, West Bandung district, Tasikmalaya city, and Kuningan city that gathered in West Java, Indonesia. Qualitatative data were obtained by using five packages of Scienve Virtual Test (SVT) with topic on integrated concepts â€œliving things and environmental sustainabilityâ€ and separated concepts â€œheat and matter; human digestive systemâ€. Results showed that general achievement of studentsâ€™ critical thinking was 58.24%. Its mean in â€˜mediumâ€™ level. The highest score on element â€œinterpretation and inferenceâ€ (66.18%) while the lowest score on element â€œquestion at issueâ€ (42.02%). Therefore, the strategy to improve of studentsâ€™ critical thinking is needed.